Genetic diversity in wild and breeding populations and clones of Eucalyptus urophylla and Eucalyptus grandis - Rocha, Guilherme N. da; Sebbenn, Alexandre M. [UNESP]; Araujo, Marcio; Costa, Leonardo O. S. da; Novaes, Evandro; Miranda, Aline C.; Moraes, Mario L. T. de [UNESP]; Lee, Davi J.; Grattapaglia, Dario; Silva, Paulo H. M. da (Sciendo, 2025)
Brazil has a long history of intensive silviculture with Eucalyptus species, mainly Eucalyptus urophylla and E. grandis. However, breeding advances may reduce genetic diversity in bred populations. Nine microsatellite markers assessed genetic diversity in wild and improved populations of E. urophylla and E. grandis, and genetic similarity in nine widely planted clones. Four wild populations of E. urophylla were evaluated: Flores, Timor-Leste, Timor and other Islands, along with three improved populations. For E. grandis, one wild and one improved population were analyzed. Results showed higher genetic diversity in improved populations, possibly due to admixed composition from different provenances. Wild populations of E. urophylla formed two distinct groups. All clones were genetically similar to improved E. urophylla populations. Some clones are inter-specific hybrids, contradicting their reported pedigree, but predominantly E. urophylla.
Keywords: Eucalyptus; genetic diversity; hybrid clones; microsatellite markers; tree improvement